Arab-Iranian relations dynamics of conflict and accommodation - Hunter, Shireen 1945- (Rowman & Littlefield International, 2019)
By highlighting the complex set of factors and their interactions that have shaped Arab-Iranian relations, the book hopes to be a corrective to the simplistic and reductionist interpretations of these relations
Keywords: Außenpolitik; Iran; Arabische Staaten; Iran / Foreign relations / Arab countries; Arab countries / Foreign relations / Iran; Diplomatic relations; Arab countries